Competition-free gaps are essential for the germination and recruitment of alpine species along an elevation gradient in the European Alps - Vera Margreiter; Janette Walde; Brigitta Erschbamer (Alpine Botany, 2021)
Seed germination and seedling recruitment are key processes in the life cycle of plants. They enable populations to grow, migrate, or persist. Both processes are under environmental control and influenced by site conditions and plant–plant interactions. Here, we present the results of a seed-sowing experiment performed along an elevation gradient (2000–2900 m a.s.l.) in the European eastern Alps. We monitored the germination of seeds and seedling recruitment for 2 years. Three effects were investigated: effects of sites and home sites (seed origin), effects of gaps, and plant–plant interactions. Seeds of eight species originating from two home sites were transplanted to four sites (home site and ± in elevation). Seed sowing was performed in experimentally created gaps. These gap types (‘gap + roots’, ‘neighbor + roots’, and ‘no-comp’) provided different plant–plant interactions and competition intensities. We observed decreasing germination with increasing elevation, independent of the species home sites. Competition-released gaps favored recruitment, pointing out the important role of belowground competition and soil components in recruitment. In gaps with one neighboring species, neutral plant–plant interactions occurred (with one exception). However, considering the relative vegetation cover of each experimental site, high vegetation cover resulted in positive effects on recruitment at higher sites and neutral effects at lower sites. All tested species showed intraspecific variability when responding to the experimental conditions. We discuss our findings considering novel site and climatic conditions.